Two noteworthy Calea (Asteraceae: Neurolaeneae) from contact areas of the Atlantic Forest and Cerrado of Brazil - Bueno, Vinicius R.; Cassol, A. P. V.; Leroy, C. J.; Bueno, M. L.; Heiden, Gustavo (Phytotaxa, 2023)
Systematic studies in the Calea myrtifolia complex have revealed two noteworthy new taxa from the contact, relict and transitional areas of the Atlantic Forest and Cerrado domains in Brazil: Calea grandiflora and Calea × parviantha, both having been treated as C. myrtifolia, now considered endemic to Minas Gerais state, Brazil. Thus, we herein provide morphological descriptions, illustrations, geographical distribution maps and discuss their taxonomic affinities. Moreover, their potential distributions are predicted. Calea grandiflora is related to C. arachnoidea and is recognized by the basal acrodromous venation (vs. semicraspedodromous), outer phyllary series 12.2–20 × 4.2–10.6 mm long (vs. 9–12 × 3–5 mm), and ray floret corolla 16.9–31 mm long (vs. 10–12 mm). Calea × parviantha is a new nothospecies, supported by a unique set of character states partially shared with the parental species C. parvifolia and C. triantha. The new hybrid species has intermediate morphology, as demonstrated by a multivariate analysis. It differs from C. parvifolia by the hispid, hispidulous or glabrous stems (vs. puberulous or puberulent) and coriaceous leaves (vs. chartaceous leaves), and from C. triantha by the rounded leaf base, sometimes subcordate (vs. cordate) and pappus scales 1.1–2.7 mm long (vs. 0.8–1.3 mm). Furthermore, we provide a taxonomic key for Calea in the states of São Paulo and Paraná.